Multiple Births, Birth Quality and Maternal Labor Supply: Analysis of IVF Reform in Sweden - Sonia R. Bhalotra; Damian Clarke; Hanna Mühlrad; Mårten Palme (Institute of Labor Economics (IZA), 2019)
In this study we examine the passage of a reform to in-vitro fertilization (IVF) procedures in Sweden in 2003. Following publication of medical evidence showing that pregnancy success rates could be maintained using single rather than multiple embryo transfers, the single embryo transfer (SET) was mandated as the default IVF procedure. Using linked registry data for the period 1998-2007, we find that the SET reform was associated with a precipitous drop in the share of multiple births of 63%. This narrowed differences in health between IVF and non- IVF births by 53%, and differences in the labor market outcomes of mothers three years after birth by 85%. For first time mothers it also narrowed the gap in maternal health between IVF and non-IVF births by 36%. Our findings imply that more widespread adoption of SET could lead to massive gains, reducing hospitalization costs and the foregone income of mothers and improving the long-run socioeconomic outcomes of children. This is important given that the share of IVF facilitated births exceeds 3% in several industrialized countries and is on the rise.
Keywords: J13; I11; I12; I38; J24; 330; IVF; fertility; maternal health; neonatal health; career penalty; human capital formation